Aerosol Dynamics in the Respiratory Tract of Food-Producing Animals: An Insight into Transmission Patterns and Deposition Distribution - Longhuan Du; Mohan Qiu; Zengrong Zhang; Chenming Hu; Li Yang; Zhuxiang Xiong; Jiangxian Wang; Xia Xiong; Han Peng; Jialei Chen; Shiliang Zhu; Xiaoyan Song; et al. (Animals)
Airborne diseases pose a significant challenge in intensive livestock farming due to their rapid transmission. Aerosols facilitate the spread of pathogens, introducing external infections to farms and enabling cross-transmission within barns. To address knowledge gaps in aerosol dynamics in animal respiratory tracts and enhance understanding of airborne disease transmission, this study employed CT scanning, 3D printing, and CFD technologies to develop and validate a pig respiratory model. Qualitative and quantitative results from the present study reveal spatiotemporal heterogeneity in aerosol deposition and transmission. Under rest conditions, for aerosols with D ≤ 5.0 μm, 21.1% of inhaled aerosols were deposited in the lung by the end of a respiratory cycle. Doubling the respiratory cycle or the inhalation rate could further increase the penetration ability of small-sized aerosols by approximately 60% to 70%. Moreover, the asymmetric distribution of airflow between the left and right halves of the lower respiratory tract (QL/R = 0.89) resulted from the leftward position of the pig’s heart and consequently led to a deposition ratio of about 0.83 between the left and right bronchial airways. These findings provide fundamental scientific data for the development and application of aerosolized vaccines and offer insights into optimizing respiratory intervention strategies.